Determinants of intention towards indebtedness amongst government servants : Moderating effect of accounting literacy and financial literacy. - Asli, Ani Asmaa (2022)
Worsen household debts annihilate financial vulnerability as government servants in a fraction of the emerging economy, Malaysia is not to be missed. Debt proliferations are what they are likely to defer to increase personal indebtedness, thus can lead to bankruptcy. Sequel to the theory of planned behaviour (TPB) adopted as the theoretical underpinning, the present study examines the moderating effects of accounting literacy and financial literacy on the relationship between the intention towards indebtedness and its determinants. The independent variables under consideration are attitude towards indebtedness, subjective norms, perceived behavioural control, lifestyle, religious obligation, and risk behaviour. A total of 377 respondents from Northern Malaysia were drawn to elicit data through self-administered survey questionnaires. Structural equation modelling (SEM) was used to analyse the data through partial least square (PLS) path modelling. A total of twenty hypotheses were tested, of which eight are on direct relationship while twelve are with the moderating effects. The result shows that; seven hypotheses, representing 35% of the total, are supported. Of this number, four have a direct significant relationship with the intention towards indebtedness, while the remaining three have reflected a significant relationship through the moderating effect of accounting literacy and financial literacy. The study concluded by highlighting the practical, methodological, and theoretical implications. Finally, limitations are discussed, and recommendations for further research are provided. If the recommendations are followed, they may help the government, policymakers, regulators, practitioners, and other stakeholders mitigate the negative consequences of accounting illiteracy and financial illiteracy among government employees throughout Malaysia.